Functional analysis and its applications : proceedings of the International Conference on Functional Analysis and its Applications, dedicated to the 110th anniversary of Stefan Banach, May 28-31, 2002, Lviv, Ukraine /: proceedings of the International Conference on Functional Analysis and its Applications, dedicated to the 110th anniversary of Stefan Banach, May 28-31, 2002, Lviv, Ukraine. (2004) - Unknown
No abstract available